Foraging strategy impacts plastic ingestion risk in seabirds. Issue 1 (15th November 2019) - Caldwell, Aliya; Seavey, Jennifer; Craig, Elizabeth
Abstract: Plastic debris is a pervasive environmental challenge described as a worldwide crisis for marine life, and seabirds are particularly sensitive to the pollutant. Seabirds exhibit a range of foraging strategies, from generalist scavengers to specialist predators, which likely influences their risk of plastic ingestion. Our study evaluates this relationship using two congeneric seabirds, including a generalist species (the Herring Gull, Larus argentatus ) and a more specialist species (the Great Black‐backed Gull, Larus marinus ) nesting in the Gulf of Maine. Analysis for stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N) was used to evaluate interspecific differences in diet and niche size, while dietary samples were collected for analysis of plastic ingestion. Herring Gulls exhibited significantly larger isotopic niche size and displayed significantly higher rates of plastic ingestion than Great Black‐backed Gulls ( p value < 0.01), though the range of physical characteristics and relative size of plastics in the diet did not differ significantly.